Interactive and passive mixed reality distraction: effects on cold pressor pain in adults - Murray, Jamie G.; Caes, Line (Frontiers in Pain Research, 2024)
While interactive distractors are predicted to be more effective in reducing acute pain than passive distractors, the underlying mechanisms remain poorly understood. Previous work using Virtual-Reality (VR) has suggested that interactive distraction may be enhanced by increasing the person's sense of immersion. Despite the possible utility of immersive VR in reducing pain, some people report being disoriented and motion sick, and it doesn't allow for interactions with environment (e.g., following instructions from medical staff). Here, we explore the role of the immersion in the effectiveness of interactive distraction by employing an alternative technology, a Mixed-Reality (MR) headset that limits disorientation by projecting virtual objects into the real world. Healthy volunteers (18–35 years) participated in two experiments employing either a between (N = 84) or a within-subject (N = 42) design to compare Interactive and Passive distraction tasks presented via MR or a standard computer display. For both experiments, a cold-pressor task was used to elicit pain, with pain tolerance and pain perception being recorded. Analysis revealed that whilst interactive distraction was more effective in reducing pain perception and increasing pain tolerance than passive distraction, the interpretation of results was sensitive to experimental design. Comparison of devices did not reveal significant differences in pain tolerance or pain intensity, while pain unpleasantness was significantly reduced during the MR task using a within-subject design. Our findings add to existing VR studies reporting little additional analgesic benefit of new, immersive technologies compared to traditional computers, but underscores the important impact the choice of experimental design can have on the interpretation of results.